2003
DOI: 10.1177/1049731502250404
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Evidence-Based Practice: Toward a New Paradigm for Social Work Education

Abstract: The scientific literature relevant to social work practice has grown expansively in recent years. Corollary developments, including the widespread availability of electronic bibliographic databases, improved indexing services, and increased acceptance of systematic reviews and evidence-based practice guidelines, have made research findings increasingly accessible to practitioners. For the first time in the history of the profession, social work educators are confronted with the challenges posed, and opportunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
136
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(144 citation statements)
references
References 21 publications
2
136
0
3
Order By: Relevance
“…There are many barriers to implementing ESTs and more research is needed to understand the best ways to implement these treatments in daily community practice (Mullen et al 2008 Addis et al 1999;Baumann et al 2006;Galinsky et al 2006;Howard et al 2003;Kendall and Beidas 2007;Nelson et al 2006;Rosen 2003;Weissman et al 2006), we have identified five common barriers to implementation. Furthermore, we also suggest possible measures that may help guide the implementation of ESTs.…”
Section: Implementing Ests For Childhood Anxiety Disorders: Barriers mentioning
confidence: 92%
“…There are many barriers to implementing ESTs and more research is needed to understand the best ways to implement these treatments in daily community practice (Mullen et al 2008 Addis et al 1999;Baumann et al 2006;Galinsky et al 2006;Howard et al 2003;Kendall and Beidas 2007;Nelson et al 2006;Rosen 2003;Weissman et al 2006), we have identified five common barriers to implementation. Furthermore, we also suggest possible measures that may help guide the implementation of ESTs.…”
Section: Implementing Ests For Childhood Anxiety Disorders: Barriers mentioning
confidence: 92%
“…In recent years there has been an increased emphasis on the use of evidence-based programs (EBPs) in social service settings (e.g., Fraser 2004; Gira et al 2004;Howard et al 2003). EBPs are ''interventions for which there is consistent scientific evidence showing that they improve client outcomes'' (Drake et al 2001: 180).…”
mentioning
confidence: 98%
“…The practice involves interaction with the environment (people, places, objects) in order to acquire new knowledge (Zahorik, 1995;Fletcher, 2009). Experimentation, in entrepreneurship education, borrows from theories related to problem-based learning (Barrows, 1985), evidence-based learning (Howard et al, 2003), and sensemaking (Weick, 1995). Problem-based learning induces cognitive conflict as a stimulus for learning and evidencebased learning encourages the use of existing information, though often incomplete, as a starting point for generating new knowledge.…”
Section: The Practice Of Experimentationmentioning
confidence: 99%